Determinants of improvement of left ventricular mechano-energetic efficiency in hypertensive patients - Lembo, Maria; Trimarco, Valentina; Manzi, Maria Virginia; Mancusi, Costantino; Esposito, Giovanni; Esposito, Salvatore; Morisco, Carmine; Izzo, Raffaele; Trimarco, Bruno (Frontiers in Cardiovascular Medicine, 2022)
Background: Arterial hypertension, especially when coexisting with other cardiovascular risk factors, could determine an imbalance between myocardial energetic demand and altered efficiency, leading to an early left ventricular (LV) systolic dysfunction, even in terms of echo-derived mechano-energetic efficiency indexed for myocardial mass (MEEi). We aim to analyse an improvement in LV MEEi, if any, in a population of hypertensive patients with a long-term follow-up and to identify clinical, metabolic and therapeutic determinants of LV MEEi amelioration. Methods: 7,052 hypertensive patients, followed-up for 5.3±4.5 years, enrolled in the Campania Salute Network, underwent echocardiographic and clinical evaluation. LV MEEi was obtained as the ratio between stroke volume and heart rate and normalized per grams of LV mass and ΔMEEi was calculated as difference between follow-up and baseline MEEi. Patients in the highest ΔMEEi quartile (≥0.0454mL/s/g)(group 1) were compared to the merged first, second and third quartiles(<0.0454mL/s/g)(group 2). METS-IR (Metabolic Score for Insulin Resistance), an established index of insulin sensitivity, was also derived. Results: Patients with MEEi improvement experienced a lower rate of major cardiovascular events (p=0.02). After excluding patients experiencing cardiovascular events, patients in group1 were younger (p<0.0001), less often diabetic (p=0.001) and obese (p=0.035). Group 1 experienced more frequently LV mass index reduction, lower occurrence of LV ejection fraction reduction, and had a better metabolic control in terms of mean METS-IR during the follow-up (all p<0.0001). Beta-blockers were more often used in group 1 (p<0.0001) than group 2. A logistic regression analysis showed that younger age, lower mean METS-IR values, more frequent LV mass index reduction and therapy with beta-blockers were significantly associated with LV MEEi improvement, independently of presence of diabetes and obesity. Conclusions: Metabolic control and therapy with beta-blockers could act in a synergic way, determining an improvement in LV MEEi in hypertensive patients over time, possibly confining cardiac damage and hampering progression towards heart failure.